Analysis Of Fbb Block (Fore Bulbous Bow) Scheduling Using The PDM Method (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Shipyards play a direct role in the development of maritime transportation in Indonesia. A shipyard is a special place equipped with facilities to support the process of building, repairing and maintaining ships. Scheduling is an important part of a new ship building project, apart from prioritizing a minimum budget and maximizing project quality. Careful project scheduling planning will support the achievement of production targets, both in quantity and quality. A shipyard in Surabaya must have its own innovation and advantages to face these challenges in order to compete with domestic and foreign shipbuilding companies. Therefore, work scheduling must be prepared using effective and efficient methods. In determining scheduling, there are several influencing factors, such as the number of workers, level of work difficulty, production facilities, and material availability. This research aims to optimize processing time planning for ship X's FBB block (rescheduling) based on various delay factors to obtain the fastest processing time for the production process. The results of accelerating critical activities using the PDM method with the alternative of additional labor are considered more efficient, where the actual duration can be accelerated by 35.6%.
Keywords: bulbous bow; scheduling; PDM